Towards Sustainable Development in Road Safety: Assessing Public Awareness on Basic Road Traffic Practices in Batu Pahat, Johor - Tukirin, Amirul Naqiuddin; Ahmad Termida, Nursitihazlin; David Daniel, Basil; Ab Ghani, Ahmad Raqib (International Journal of Integrated Engineering, 2023)
Road accident contributes to high fatality rate around the world and being the 8th leading cause of death of all ages worldwide. Thus, road safety is essential for ensuring the safety and security of individuals of all ages, as well as reducing the number of traffic accidents and injuries as a one way to achieve Sustainable Development Goals 2030. This study aims to assess the level of road safety awareness in terms of basic road traffic practices among public who use Jalan Kluang Federal Route 50 (FT050). The level of knowledge on basic road traffic practices, the level of perceived real practice on basic road traffic practices, and the relationship between their level of knowledge and perceived real practice on basic road traffic practices were investigated. A survey method via questionnaire was distributed randomly to 200 respondents who are adults aged 18 and above and who live around Batu Pahat areas using Google Form online platform. Relevant statistical methods via Statistical Package for the Social Science Software version 26.0 (SPSS) such as descriptive, Mean Score Method, Correlation and Regression analyses were used to analyse the data.  It is found that the level of knowledge on basic road traffic practices among public is high.  Meanwhile, the level of perceived real practice on basic road traffic practices among public is low. Regression analysis results show that the awareness on knowledge of basic road traffic practices variable (? = 0.624, t = 11.229, p < 0.05) demonstrate a statistically significant relationship with perceived real practices, indicating that, the better an individual’s awareness on knowledge of basic road traffic practices (e.g. importance of safety belt, safety helmet, child restraint system (CRS) and speeding) the better the individual to actually apply the basic road traffic practices (e.g. the use of seat belt, safety helmet, CRS and speeding).